2016
DOI: 10.1111/bpa.12373
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis and Spreading of Normal and Aberrant α‐Synuclein

Abstract: It is now established that α-synuclein can be physiologically secreted to the extracellular space. In this sense, mechanisms that govern the secretion of the protein may be of importance in the initiation and progress of synucleinopathies. It is possible that increased secretion may aid the formation of toxic seeds extracellularly. Alternatively, reduced presence of extracellular α-synuclein due to impaired secretion may increase the intracellular load and trigger intracellular seeding. Once outside, α-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 57 publications
0
50
0
Order By: Relevance
“…In cell cultures, α-synuclein is released via exocytosis and the process is enhanced by cellular stress such as inhibition of lysosomes (66–70). A minor portion (frequently estimated at around 5%) of the extracellular α-synuclein is associated with exosomes and it can be present in oligomeric forms, both on the inside and surface of the microvesicles (68,69,71,72). It is unclear whether all of the α-synuclein found in the exosomal fraction is secreted with the exosomes or whether they associate with each other outside the cell.…”
Section: Cellular and Molecular Mechanisms Of α-Synuclein Intercellulmentioning
confidence: 99%
“…In cell cultures, α-synuclein is released via exocytosis and the process is enhanced by cellular stress such as inhibition of lysosomes (66–70). A minor portion (frequently estimated at around 5%) of the extracellular α-synuclein is associated with exosomes and it can be present in oligomeric forms, both on the inside and surface of the microvesicles (68,69,71,72). It is unclear whether all of the α-synuclein found in the exosomal fraction is secreted with the exosomes or whether they associate with each other outside the cell.…”
Section: Cellular and Molecular Mechanisms Of α-Synuclein Intercellulmentioning
confidence: 99%
“…At the subcellular level, it has been observed that, in neurons, α -synuclein can be found in the three endosomal compartments and translocate across them (early, late, and recycling endosomes) [32]. This pathway could be involved in the process of protein release [32].…”
Section: Mechanisms Of α-Synuclein Releasementioning
confidence: 99%
“…This pathway could be involved in the process of protein release [32]. Moreover, treatments that could disturb the homeostasis of the endosomal system alter α -synuclein spreading [63, 157].…”
Section: Mechanisms Of α-Synuclein Releasementioning
confidence: 99%
See 1 more Smart Citation
“…This is critical to understand disease propagation through synaptically connected regions along the whole CNS. In this way, VPS mutations may be a pivot to understand cell-to-cell transmission of protein cargoes through exosomes (Danzer et al, 2012; Poehler et al, 2014; Tsunemi et al, 2014; Emmanouilidou and Vekrellis, 2016; Lööv et al, 2016; Figure 1). Thus, an in depth analysis of VPS alterations is expected to disclose the anatomical basis of disease progression as recently described (Hawkes et al, 2010; Del Tredici and Braak, 2013; Holmqvist et al, 2014; Garcia-Esparcia et al, 2015; Lamberts et al, 2015).…”
Section: Vps and Neurobiology Of Pdmentioning
confidence: 99%